Impact of familiarity and green image on satisfaction and loyalty among young green hotel's guests - a developing country's perspective - Wang, Lei; Zhang, Qi; Wong, Philip Pong Weng* (Frontiers Media, 2022)
Familiarity and green image influencing travelers’ green hotel patronage have often been overlooked in previous research. The aim of this study was to examine the relationship of the two dimensions of familiarity and the two dimensions of image with the overall image, satisfaction, and loyalty. The theoretical research model used in this study was based on the stimulus–organism–response framework. The research design for this study employed a quantitative approach using a purposive sampling method involving 488 student responses. The tests of the proposed hypotheses were conducted using SPSS and AMOS. The results of the study showed that experiential familiarity and informational familiarity positively influenced cognitive image and affective image, respectively, while cognitive image had a positive influence on the affective image. In addition, cognitive and affective images have a positive influence on the overall image, and the overall image is shown to have a positive impact on satisfaction and loyalty. Finally, satisfaction was found to have a positive influence on loyalty, while satisfaction plays a partial meditation role in the relationship between overall image and loyalty.